First get the recognition - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
'In Senegal there is a tremendous growth of women s organisations and associations in community neighbourhoods. Women are organising themselves to alleviate poverty, since it affects them more than it does men. Illiteracy, lack of training and...